Características psicoambientales asociadas al inicio, curso y desarrollo de patologías alérgicas: una revisión general del fenómeno - Cortés R., Aarón (Revista Hospital Clínico Universidad de Chile, 2012)
Objective: To systematically review all available studies that pursued the development of a questionnaire to evaluate the relationships between psychological, social and environmental characteristics and their relationship with the onset, course and development of allergies. Methods: Studies were identified using MedlinePlus and PubMed until August 2011. Results: No publications related to the development of questionnaires evaluating the described relationship were found. However, nine studies were selected to collect relevant data on this topic. The studies were divided related to 3 areas: neuro-immune interactions, genetics influences andpsycho-social factors. Enough compelling evidence was found for an association between psychosocial factors with atopic diseases; the role of the family is highlighted as an important social factor influencing psychological and atopic variables and; evidence of an inhibition on the hypothalamus-pituitary-adrenal (HPA) axis and an overreaction of the sympathetic adrenomedullary (SAM) system to psychological stress among patient with atopic dermatitis were found. Conclusion: In atopic diseases the psychosocial characteristics of the affected person, his/her immune and sympathetic system and his/her social environment appear to be related to the onset, course and development of allergic condition.